Relationship between peripheral airway dysfunction, airway obstruction, and neutrophilic inflammation in COPD. Issue 10 (28th September 2004) - O'Donnell, R A; Peebles, C; Ward, J A; Daraker, A; Angco, G; Broberg, P; Pierrou, S; Lund, J; Holgate, S T; Davies, D E; Delany, D J; Wilson, S J; et al.
Abstract : Background: Considerable research has been conducted into the nature of airway inflammation in chronic obstructive pulmonary disease (COPD) but the relationship between proximal airways inflammation and both dynamic collapse of the peripheral airways and HRCT determined emphysema severity remains unknown. A number of research tools have been combined to study smokers with a range of COPD severities classified according to the GOLD criteria. Methods: Sixty five subjects (11 healthy smokers, 44 smokers with stage 0–IV COPD, and 10 healthy non-smokers) were assessed using lung function testing and HRCT scanning to quantify emphysema and peripheral airway dysfunction and sputum induction to measure airway inflammation. Results: Expiratory HRCT measurements and the expiratory/inspiratory mean lung density ratio (both indicators of peripheral airway dysfunction) correlated more closely in smokers with the severity of airflow obstruction ( r  = −0.64, p<0.001) than did inspiratory HRCT measurements (which reflect emphysema severity; r  = −0.45, p<0.01). Raised sputum neutrophil counts also correlated strongly in smokers with HRCT indicators of peripheral airway dysfunction ( r  = 0.55, p<0.001) but did not correlate with HRCT indicators of the severity of emphysema. Conclusions: This study suggests that peripheral airway dysfunction, assessed by expiratory HRCT measurements, is a determinant of COPD severity. Airway neutrophilia, a central feature of COPD, is closely associated with the severity of peripheral airway dysfunction in COPD but is not related to the overall severity of emphysema as measured by HRCT.